Molecular and physiological responses of two quinoa genotypes to drought stress - Zhu, Xiaolin; Liu, Wenyu; Wang, Baoqiang; Yang, Ling (Frontiers in Genetics, 2024)
Quinoa is an important economic food crop. However, quinoa seedlings are susceptible to drought stress, and the molecular mechanism of drought tolerance remains unclear. In this study, we compared transcriptomic and physiological analyses of drought-tolerant (L1) and susceptible (HZ1) genotypes exposed to 20% PEG for 3 and 9 days at seedling stage. Compared with HZ1, drought stress had less damage to photosynthetic system, and the contents of SOD, POD and CAT were higher and the contents of H2O2 and O2 -were lower in L1 leaves. Based on the RNA-seq method, we identified 2423,11856,1138 and 3903(HZ1-C3-VS-T3, HZ1-C9-vs-T9, L1-C3-vs-T3 and L1-C9-vs-T9) annotated DEGs. Go enrichment was shown in terms of Biological Process: DEGs involved in biological processes such as metabolic process, cellular process, and single-organism process were most abundant in all four comparison treatments. In Molecular Function: the molecular functions of catalytic activity, binding and transporter activity have the most DEGs in all four processes. Cellular Component: membrane, membrane part, and cell have the most DEGs in each of the four processes. These DEGs include AP2/ERF, MYB, bHLH, b-ZIP, WRKY, HD-ZIP, NAC, C3h and MADS, which encode transcription factors. In addition, the MAPK pathway, starch and sucrose metabolism, phenylpropanoid biosynthesis and plant hormone signal transduction were significantly induced under drought stress, among them, G-hydrolases-66, G-hydrolases-81, G-hydrolases-78, Su-synthase-02, Su-synthase-04, Su-synthase-06, BRI1-20 and bHLH17 were all downregulated at two drought stress points in two genotypes, PP2C01, PP2C03, PP2C05-PP2C07, PP2C10, F-box01 and F-box02 were up-regulated at two drought stress points in two genotypes. These results agree with the physiological responses and RNAseq results. Collectively, these findings may lead to a better understanding of drought tolerance, and some of the important DEGs detected in this study could be targeted for future research. And our results will provide a comprehensive basis for the molecular network that mediates drought tolerance in quinoa seedlings and promote the breeding of drought-resistant quinoa varieties.